The Present International Situation: Civilization, Ideology, Elite - M. V. Alexandrov (MGIMO University Press, 2016)
The Present International Situation: Civilization, Ideology, Elites / A.I.Podberezkin, V.G.Sokolenko, S.R. Tsyrendorzhiev. Moscow: MGIMO-University, 2015. 464p.